Problem-Based Learning: An intervention proposal for the teaching of Geosciences in Vocational and Technological Education (Research, Society and Development, 2022)
Problem-Based Learning (PBL) seeks to make students more independent, providing opportunities for them to take responsibility for their learning process. In this sense, we selected the PBL as an active teaching methodology for the development of this work. The research in question intends to use the PBL as a pedagogical intervention instrument in the teaching of Geosciences in Professional and Technological Education, in a class of the 6th period of an Integrated Technical Course, in the Youth and Adult Education modality, at the Federal Institute of Goiás. To achieve this objective, some pre-defined methodologies were used, such as: prior explanation of the content to situate students on the subject; use of the problem-question to instigate them to develop critical and autonomous thinking; quizzes to express your knowledge before and after watching educational videos; and, finally, a new questionnaire to assess the proposed methodology. As a result, we realized that 100% of the students approved the methodology used, which allows us to conclude that the intervention proposal was successful.